Production of epoxidized palm oil – derived oleic acid by using acidic ion exchange resin (AIER) : epoxidation method and kinetic study / Muhammad Amir Syazwan Che Mamat Azman, Jumain Mohd Jalil and Aliff Farhan Mohd Yamin - Che Mamat Azman, Muhammad Amir Syazwan; Mohd Jalil, Jumain; Mohd Yamin, Aliff Farhan (2021)
This research done to study the epoxidation reaction for different parameters such as type of catalyst used and agitation speed. The fatty acid content in vegetable oil will undergo epoxidation reaction to produce epoxide. The process start with the formic acid (FA) will react with hydrogen peroxide (H2O2) in order to produce performic acid (PFA) in aqueous and side product is water (H2O). Then, transfer of acid in aqueous ,PFA (aq) to the oil phase, PFA (oil). Meanwhile, the PFA (oil) will react with oleic acid (OA) to produce epoxy oleic acid (EOA) and formic acid (FA) in oil phase. Finally, the transfer of carboxylic acid to the aqueous phase. Besides, kinetic study also be carried by develop a single phase kinetic model to determine the value of kinetic rate constant, k for every reaction via MATLAB simulation. From the results of simulation data, this research highlights on the comparison between experimental and simulation data that has been obtained. In addition, effect of catalyst used and different level of agitation speed on the value of k also has been studied.